The godfather [compact disc, unabridged] - Puzo, Mario, 1920-1999 (Brilliance Audio, 2011)
More than forty years ago, Mario Puzo wrote his iconic portrait of the Mafia underworld as told through the fictional first family of American crime, the Corleones. The leader, Vito Corleone, is the Godfather. He is a benevolent despot who stops at nothing to gain and hold power. His command post is a fortress on Long Island from which he presides over a vast underground empire that includes the rackets, gambling, bookmaking, and unions.